Marija Jurić Pahor: Das Gedächtnis des Krieges. Die Isonzofront in der Erinnerungsliteratur von Soldaten und Zivilisten: Klagenfurt/Celovec: Hermagoras Verlaag/Mohorjeva založba, 2017, 444 str. - Čeh Steger, Jožica (Slavia Centralis, 2020)
The article presents a monograph by Marija Jurić Pahor entitled Das Gedächtnis des Krieges. Die Isonzofront in der Erinnerungsliteratur von Soldaten und Zivilisten (Memory of the War. Isonzo Front in the Memorial Literature of Soldiers and Civilians), in which the author deals with the question of how the destructive power of the First World War entered the memory of soldiers and civilians in the case of one of the worst military front, which took place between Austria-Hungary and Italy in the Soča area.